Essential oil analysis and biological activities of the aerial parts of Zygophyllum eichwaldii C. A. Mey., a native plant from Iran - Asma Mazoochi; Seied Ali Pourmousavi; Abdolhamid Bamoniri (Institue of Medicinal Plants, ACECR, 2021)
Background: Zygophyllum eichwaldii C. A. Mey. is a medicinal plant from Zygophyllaceae family. This family consists of 27 genera and 285 species. Objective: The present study was performed to evaluate the chemical composition of the essential oil of Z. eichwaldii and evaluation of biological activities of its extracts .Methods: Essential oils extraction of Z. eichwaldii aerial parts was performed by three different procedures and its chemical composition were evaluated by GC and GC-MS analyses. Evaluation of the biological activities was carried out by spectrophotometric methods. Results: GC-MS analysis showed menthol, thymol and palmitic acid as major components of the plant essential oils. In biological activity evaluation, while methanol extract showed moderate to week potency in antioxidant assessments, the ethyl acetate fraction was strong in these tests (IC50 = 178.63 µg/ml in DPPH assay and 70.52 % inhibition in β-carotene/linoleic acid tests). This fraction also showed significant phenol, flavonoid and tannin contents (99.83, 118.29 and 188.05 μg/mg, respectively). Also, plant extracts exhibited considerable antimicrobial activities against most selected bacteria. Conclusion: Significant amount of phenol, flavonoid and tannin compounds in the ethyl acetate fraction and high antimicrobial activity against most bacterial strains, candidates this plant as a good case for further studies in this respect.